FAKTOR-FAKTOR YANG BERHUBUNGAN DALAM PELAKSANAAN ASUHAN KEPERAWATAN DI RUMAH SAKIT - Gena Devitria; Kristina Everentia Ngasu; Zahra Maulidia Septimar (Nusantara Hasana Berdikari, 2021)
The implementation of nursing care is a never-ending cycle so nurses are required to use the nursing process and participate in activities that can lead to improvements in the nursing process. This study aims to determine the description of theories, findings and research results from previous researchers so as to get an overview of the factors that are related to the implementation of nursing care in hospitals. The study was conducted using a literature review as a guide to search for research articles obtained from the internet using the Google Scholar site and articles were filtered using the PRISMA method. Based on the 11 journal articles reviewed that the factors related to the implementation of nursing care there are several factors that are related to the implementation of nursing care, namely: knowledge, nurse-patient ratio or workload, lack of inadequate facilities, work environment, related problems salary, and awards or rewards.